Public, Opinion, and Public Services in Public Relations Activities - Lailatul Nadia Permata Putri; Lilik Sulistiyaningsih; Mohammad Ali Maki; Umi Maslihah; Khusnul Khotimah (Islamic Studies in the World, 2024)
Background. The relationship between public opinion and public service in the context of public relations activities. Public opinion is a view or opinion held by the public on an issue or public policy. Meanwhile, public services are the efforts of the government or public institutions in providing services to the community. Public relations activities have an important role in building good relationships between the government or public institutions and the public through effective communication. Purpose. This research aims to find out the definition of iternal and external relations itself, as well as to find out what are the ways and/or techniques to build internal and external relations in educational institutions. Method. This research uses a type of library research. data sources are obtained through secondary data sources in the form of e-journals, e-books, papers, articles, and other relevant research. After the sources obtained from various data were collected, the next step was data processing which was processed in accordance with the research code of ethics. Furthermore, data analysis uses descriptive analysis. Results. Building good relationships between internal publics in educational institutions and with external parties outside educational institutions needs to be done considering the management of these relationships can advance the school and improve the good image of the school. And in building relationships with internal and external parties, educational institutions cannot be done just like that without the right techniques because of the different characteristics of each party. For this reason, the right way and/or technique is needed to build internal and external relationships in educational institutions. Conclusion. Public Relations (PR) is a field that focuses on interaction and communication with various groups of people, referred to as publics or audiences. The public in PR includes individuals and institutions that interact directly or indirectly with an organisation. The PR function involves managing relationships with these publics to achieve organisational goals, both through internal and external PR.